Author Correction: Human milk oligosaccharide 2'-fucosyllactose promotes melanin degradation via the autophagic AMPK–ULK1 signaling axis (Scientific Reports, (2022), 12, 1, (13983), 10.1038/s41598-022-17896-4) - Heo, Hyojin; Cha, Byungsun; Jang, Dongmin; Park, Chaewon; Park, Gunwoo; Kwak, Byeong Mun; Bin, Bum Ho; Park, Ji Hwan; Lee, Mi Gi (Scientific Reports, 2022)
In the original version of this Article Dongmin Jang was omitted from the equally contributing authors statement. “These authors contributed equally: Hyojin Heo and Byungsun Cha”. now reads: “These authors contributed equally: Hyojin Heo, Byungsun Cha and Dongmin Jang”. The original Article has been corrected.